Answer to ECG Quiz no. 30 - Millar, R. Scott (SA Heart Journal, 2017)
If a patient presents with a clinical syndrome suggesting acute  myocardial infarction and the ECG shows LBBB, treat as for ST elevation myocardial infarction (STEMI), whether or not the ECG shows features diagnostic of MI. While LBBB tends to obscure the usual features of STEMI, diagnostic features may still be present (Table I). The most useful are: concordant ST elevation of 1mm or more in any lead; discordant ST elevation of 5mm or more. Diagnostic and localising ST segment elevation may also be present in other conditions affecting ventricular depolarisation, such as paced rhythm, ventricular escape rhythms, accelerated idioventricular rhythm and pre-excitation